Layered inorganic-organic clay-like nanocomposites rearrange to form silsesquioxanes on acid treatment - Kumaraswamy, Guruswamy; Deshmukh, Yogesh S.; Agrawal, Vikrant V.; Rajmohanan, P. (Journal Physical Chemistry B, 2005)
The formation of talc-like compounds by the condensation of organotrialkoxy silanes with magnesium hydroxide has been recently reported. These represent layered hybrid nanomaterials that have a layer thickness of around 1 nm, have organic moieties covalently linked to the layer surfaces, and are called ``organoclays.'' We show that such compounds are sensitive to acid treatment. When a phenylclay is treated with hydrochloric acid, magnesium leaches out, destroying the layered structure. The extent to which magnesium is leached out is a function of the time of the acid treatment and the concentration of the acid used. Magnesium leaches out rapidly when the concentration of acid used to treat the phenyl-clay is higher, and the extent of structural magnesium that is leached out is also higher for higher acid concentrations. Removal of the magnesium rearranges the structure of the phenyl-clay to form oligomeric phenylsilsesquioxanes. FTIR and NMR suggest that the silsesquioxanes formed by acid treatment of the phenyl-clay comprise a mixture of ladderlike and cagelike structures.